Ecological versatility and the assembly of multiple competitors: cautionary notes for assembly inferences - Victor S. Saito; Fabien Laroche; Tadeu Siqueira; Sandrine Pavoine (Ecology, 2018)
The role of niche differences and competition is invoked when one finds coexisting species to be more dissimilar in trait composition than expected at random in community assembly studies. This approach has been questioned as competition has been hypothesized to either lead to communities assembled by similar or dissimilar species, depending on whether species similarity reflects fitness or niche differences, respectively. A current problem is that the arguments used to draw relationships between competition and species similarity are based on pairwise theoretical examples, while in nature competition can occurs among a constellation of species with different levels of versatility in resources used. By versatility we mean the documented ability of some species to escape competition for commonly used resources by changing for marginal and unused resources. Thus, a versatile species will have the ability to decrease niche overlap with all other species when facing strong competitors. When these species are embedded in multiple interactions the role of pairwise niche and fitness differences could be reduced due to indirect effects and thus competition would not be detectable. Here we developed a coexistence theory where competition occurs simultaneously among multiple species with different levels of versatility and then used it in a simulation to unravel patterns of species similarity during community assembly. We found that simulated communities can be assembled by species with more, less or equal similarity compared to a null model when using a mean distance based metric ( SES . MPD ). However, contrasting these varied results, we consistently found species overdispersion using a nearest neighbor‐based metric ( SES . MNTD ), even when species differences reflected more directly their competitive abilities than their niche differences. Strong tendency to overdispersion emerged when high ecological versatility promoted large niche differences and enabled coexistence. This is because versatility to use marginal resources compensates possible fitness differences among species. Our findings provide mounting evidence of the important role of minimum niche differences and versatility in resource consumption for species embedded in multiple direct and indirect interactions.